2009
DOI: 10.3155/1047-3289.59.7.790
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Environmental Parameters for Minimum Ammonium Losses during Composting of Trimming Residues

Abstract: A neural fuzzy system was used to investigate the influence of environmental variables (time, aeration, moisture, and particle size) on composting parameters (pH, organic matter [OM], nitrogen [N], ammonium nitrogen [NH 4 ϩ -N] and nitrate nitrogen [NO 3 Ϫ -N]). This was to determine the best composting conditions to ensure the maximum quality on the composts obtained with the minimum ammonium losses. A central composite experimental design was used to obtain the neural fuzzy model for each dependent variable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, different results have been found in some studies, for instance, Bueno et al (2009) reported that the NH 4 + -N concentrations increased significantly at the initial stage and then decreased during composting of trimming residues at different levels of moisture and particle size. 6, the NH 4 + -N concentrations in all piles, although occurring at different times, increased significantly at the initial stage and reached their maximum level because of ammonification which is always associated with temperature increase and mineralization of organic N compounds (Bueno et al 2009). 6, the NH 4 + -N concentrations in all piles, although occurring at different times, increased significantly at the initial stage and reached their maximum level because of ammonification which is always associated with temperature increase and mineralization of organic N compounds (Bueno et al 2009).…”
Section: N Transformationmentioning
confidence: 79%
See 3 more Smart Citations
“…However, different results have been found in some studies, for instance, Bueno et al (2009) reported that the NH 4 + -N concentrations increased significantly at the initial stage and then decreased during composting of trimming residues at different levels of moisture and particle size. 6, the NH 4 + -N concentrations in all piles, although occurring at different times, increased significantly at the initial stage and reached their maximum level because of ammonification which is always associated with temperature increase and mineralization of organic N compounds (Bueno et al 2009). 6, the NH 4 + -N concentrations in all piles, although occurring at different times, increased significantly at the initial stage and reached their maximum level because of ammonification which is always associated with temperature increase and mineralization of organic N compounds (Bueno et al 2009).…”
Section: N Transformationmentioning
confidence: 79%
“…6, the NH 4 + -N concentrations in all piles, although occurring at different times, increased significantly at the initial stage and reached their maximum level because of ammonification which is always associated with temperature increase and mineralization of organic N compounds (Bueno et al 2009). During the thermophilic phase, lower increments were detected with respect to the mesophilic phase because of the inhibitory effect of NH 3 and high temperature on the growth of nitrifying bacteria (Huang et al 2004;Bueno et al 2009). Except in test III, the NH 4 + -N contents in other piles were <400 mg/kg at the end of composting, which is the maximum limit recommended for a mature compost.…”
Section: N Transformationmentioning
confidence: 93%
See 2 more Smart Citations